Rhythm instruction to improve ESP students’ fluency: a study of pausing - Quesada Vázquez, Leticia (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
The present work is aimed at examining how efficient it is to teach language rhythm to enhance English for Specific Purposes (ESP) learners’ fluency. 298 Spanish/Catalan speakers participated in the experiment, among which 42 students fulfilled treatment and were examined as subjects of the study. For ten weeks, participants took pronunciation instruction within their regular lessons. The pronunciation sessions lasted thirty minutes and followed a communicative framework. Students were divided into an experimental group, with explicit rhythm training, and a control group, without it. The total number of pauses and unfilled pauses were counted and compared to assess their frequency performing ANOVAs and t-tests. Descriptive analysis shows that the experimental group tends to pause less and make fewer unfilled pauses after training. However, statistical significance is only reached for the independent-samples t-test of the effect sizes of the number of unfilled pauses. Therefore, these findings suggest a greater command over pausing when rhythm is explicitly taught, and a consequent improvement of fluency in the second language, despite statistical results not always being significant.